The Role Of Blockchain As A Security Support For Student Profiles In Technology Education Systems - Po Abas Sunarya; Untung Rahardja; Lusyani Sunarya; Marviola Hardini (Universitas Islam Sumatera Utara, 2020)
The sophistication of education technology (edu-tech) from the perspective of the blockchain has not been well implemented, because so far the methods used in education are still centralized and tend to be any student data such as class schedules and student profiles can be falsified. So an edu-tech research was made that applied the blockchain to facilitate learning related to the industrial revolution 4.0 and was able to optimize the delivery of information that is currently still one-way. Although there are a number of benefits that have been felt about edu-tech, digital disruptions remain, many challenges related to information security and privacy. The presence of the blockchain in security work integrated with a smartphone will be able to optimize the existing security system, authentication, and information that has been distributed in relation to student profiles, which can be assured of their originality.